Universiti Malaysia Pahang UMP seeks collab partners for B40 programme - UMP, PNC (RECODA, 2022)
A delegation from Universiti Malaysia Pahang (UMP), led by its Chairman Tan Sri Dato’ Sri Dr. Abdul Aziz Abdul Rahman, in an animated discussion with our CEO Datu Ismawi Ismuni.